The potential of black ant (Dolichoderus sp.) as a biological control agents of the coconut leaf beetle (Brontispa longissima) - Wan Khairul Anuar W. A,; M. Fahmi M.H.,; Badrulhisham I.,; M. Bakhtiar B.H.,; A. Mohd Rani,; Idris A.B., (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
The study of coconut leaf beetle infestation, Brontispa longissima on palms and the effectiveness of biological agents as a method of control have been carried out in the laboratory. The study involves the effectiveness of potential black ants as biological agents in controlling beetle populations. The results of laboratory studies on the ability of black ant predation on the B. longissima found that the percentage of mean beetle are eaten by the group that has the number 100 black ants were higher and significantly different (P <0.05) as compared to group numbers 5, 20, 50 and 75 black ants. In addition, black ants also tend to attack and devour the B. longissima larvae and pupa stage compared to adult’s beetle via laboratory studies. It can be concluded that the B. longissima beetle has a great potential for causing considerable damage to the coconut tree which could affect coconut palm industry in Malaysia. However, the usage of biological agents as a control method had shown promising results in order to control the beetle infestation in coconut palm areas.